2016
DOI: 10.1016/j.chb.2016.05.089
|View full text |Cite
|
Sign up to set email alerts
|

Online community and the personal diary: Writing to connect at Open Diary

Abstract: Open Diary was the first online diary service to be created, in existence from 1998 to 2014. An ethnographic case study was performed in 2006-2008 to explore community-creation on the site, using the theory of sense of virtual community (Blanchard & Markus, 2002, 2004) to analyse site practices and the member experience. The study describes a cohesive community based on a culture of support, empathy and open sharing of personal lives enabled by anonymity and privacy protections. The article discusses these res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Since then, much work has been produced showing that community experiences can indeed take place in a variety of online environments (e.g. Martinviita, 2016a;Obst, Zinkiewicz & Smith, 2002;Rotman, Goldberg & Preece, 2009;Welbourne, Blanchard & Boughton, 2009). This work often centres -quite understandably -on the connections among the participants, and the quality of those connections in terms of producing the feelings of belonging and shared identity associated with community experiences (see Chayko [2014] for a useful overview of the many views into online community in research thus far).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, much work has been produced showing that community experiences can indeed take place in a variety of online environments (e.g. Martinviita, 2016a;Obst, Zinkiewicz & Smith, 2002;Rotman, Goldberg & Preece, 2009;Welbourne, Blanchard & Boughton, 2009). This work often centres -quite understandably -on the connections among the participants, and the quality of those connections in terms of producing the feelings of belonging and shared identity associated with community experiences (see Chayko [2014] for a useful overview of the many views into online community in research thus far).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that some of these platforms have been active on the Internet since 1995. Despite the great transformations that the Internet has undergone, many diarists have gone on writing their online diaries on a regular basis, as they started doing more than twenty years ago (Martinviita, 2016).…”
Section: Databasementioning
confidence: 99%
“…This anonymity was one of the mainstays of popular early sites like OpenDiary.com, which was online from 1998-2014, and was important to many online diarists. In a study of Open Diary users in 2006-8, Annamari Martinviita found that many of their informants felt that the anonymity allowed them to write about very intimate details of their lives, and that the ability to communicate openly about their lives, with no fear of the conversations impacting upon their everyday lives, was very important to them 11 . With Facebook, using real names has become increasingly common in social media, but there are still many platforms where people share diary-like material either using a pseudonym or completely anonymously.…”
Section: How Technology Shapes Diariesmentioning
confidence: 99%